Model and mesh generation of partially overlapped circular hollow section k-joints for fatigue studies - Nguyen, Thi Bich Ngoc (2010)
In this study, a novel and consistent geometrical model and mesh generation technique is proposed for partially overlapped CHS K-joints with and without crack. For the mesh without crack, the geometrical model of welding details is developed both on the chord and brace sides by a new approach such that the cut off requirements by AWS (1996) and API (2000) can be satisfied. Welding parameters are verified and adjusted by the measurement of welding thickness on small and full scale specimens. Furthermore, a general algorithm is developed for the determination of the theoretical and actual intersection points between the braces and the chord, which is a distinctive feature of partially overlapped CHS K-joints. For the mesh with crack, a general model for the inclined crack surface and an unsymmetrical crack front are proposed. Based on the developed geometrical model, a new mesh modelling method is proposed for partially overlapped CHS K-joints. The mesh generator is constructed step-by-step, therefore it is able to produce several kinds of meshes such as surface meshes, solid meshes, meshes with or without welding and crack details. At each step, a particular mesh can be exported depending on the complexity of the particular fatigue problem under consideration. The application range of the mesh generator is extended for special cases of identical chord and braces dimensions as well as large overlapped percentage, which are not commonly covered by other commercial software packages. Most importantly, it is able to generate a solid mesh with welding details and surface crack of any length and locates at either sides of the joint intersection. In the experimental program, two full-scale partially overlapped CHS K-joints were tested under cyclic combined loads in order to gather more information about the fatigue performance of the joints, as well as to evaluate the surface crack model proposed. During the tests, the crack initiation and propagation were monitored.